RISK FACTORS FOR URETHROCUTANEOUS FISTULAS FORMATION AFTER ONE STAGE HYPOSPADIAS REPAIR - Fariz, Mohammad; Rodjani, Arry; Wahyudi, Irfan (Indonesian Urological Association, 2011)
Objective: To evaluate risk factors that contribute to urethrocutaneous fistulas formation after one stage hypospadias repair. Material & method: A case control study was performed on hypospadias patients that underwent one stage hypospadias repair. We analyzed the correlation of urethrocutaneous fistula formation with patient age, hypospadias classification, chordee severity, other urogenital anomalies, history of hormonal therapy, suture size, duration of operation, type of dressing, type of stent, duration of stenting, and three types of operation technique, which are TIP, Duckett, and Onlay Island Flap. Results: There were 116 patients with mean age 5,7 ± 3,9 years old (4 months – 19 years old). Urethrocutaneous fistula occured in 12 patients (10,3%). From the data analysis, we didn’t find any significant correlation between urethrocutaneous fistula formation and patient’s age (p = 0,426), hypospadias classification (p = 0,695), chordee severity (p = 0,564), other urogenital anomalies (p = 0,964), history of hormonal therapy (p = 0,739), suture size (p = 0,248), duration of operation (p = 0,856), type of dressings (p = 0,580), type of stents (p = 0,600), and duration of stenting (p = 0,796). We also didn’t find any significant correlation between urethrocutaneous fistula formation and operation technique TIP vs Duckett (p = 0,314), and TIP vs Onlay Island Flap (p = 0,644). Conclusion: There were no significant correlation between urethrocutaneous fistula formation and patient age, hypospadias classification, chordee severity, other urogenital anomalies, history of hormonal therapy, suture size, duration of operation, type of dressing, type of stent, and duration of stenting. There were also no significant correlation between urethrocutaneous fistula formation and operation technique TIP vs Duckett, and TIP vs Onlay Island Flap. Keywords: Hypospadias, one stage urethroplasty, urethrocutaneous fistula.